2013
DOI: 10.3171/2013.7.spine1362
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of lumbar discectomy and single-level fusion for spondylolisthesis: results from the NeuroPoint-SD registry

Abstract: Object. There is significant practice variation and considerable uncertainty among payers and other major stakeholders as to whether many surgical treatments are effective in actual US spine practice. The aim of this study was to establish a multicenter cooperative research group and demonstrate the feasibility of developing a registry to assess the efficacy of common lumbar spinal procedures using prospectively collected patient-reported outcome measures.Methods. An observational prospective cohort study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Obtaining such high rates of follow-up in NeuroPoint-SD required significant resource commitment from all participating institutions. For 1 year of data collection, we previously estimated a cost of more than $1800 per patient, 9 and most NeuroPoint-SD sites incurred more than $18,000 in actual costs to collect data for 1 year (Table 1). By collecting data for 3 months rather than 1 year, the costs per site would be reduced by nearly two-thirds ($7000 vs $18,500).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obtaining such high rates of follow-up in NeuroPoint-SD required significant resource commitment from all participating institutions. For 1 year of data collection, we previously estimated a cost of more than $1800 per patient, 9 and most NeuroPoint-SD sites incurred more than $18,000 in actual costs to collect data for 1 year (Table 1). By collecting data for 3 months rather than 1 year, the costs per site would be reduced by nearly two-thirds ($7000 vs $18,500).…”
Section: Discussionmentioning
confidence: 99%
“…Based on data from this registry, it was demonstrated that lumbar discectomy and lumbar spinal fusion for degenerative lumbar spondylolisthesis were effective in improving QOL using validated general and disease-specific outcome instruments, the 36-item ShortForm Health Survey (SF-36), Oswestry Disability Index (ODI), and a visual analog scale (VAS). 9 Collection of patient-reported outcomes data in NeuroPoint-SD required dedicated research personnel at multiple institutions, data management and analysis experts, and was associated with significant costs. One of the major drivers of cost, as well as the challenges to overall validity for registries, is the ability to obtain 1-year follow-up on all patients.…”
mentioning
confidence: 99%
“…9,29 In light of the expense and difficulty associated with obtaining real-world PRO data, it has been suggested that short-term outcomes data might, in certain circumstances, serve as an adequate surrogate for long-term data. 25,32,39,43 Given the logistical challenges and financial restraints of collecting long-term patient-reported data at a scalable level, it is vital to understand how well short-term outcomes represent long-term outcomes for both patient populations and individual patients.…”
mentioning
confidence: 99%
“…1,3,8,10,11,25 Some of these factors characterized smokers in our study. Furthermore, consistent with other studies, our previous analysis has demonstrated that being a smoker is associated with poor disability outcomes following lumbar spine surgery.…”
Section: Discussionmentioning
confidence: 99%